QUANTITY OF FISH MEAL PROCESSED FROM SUN-DRIED FISH IN A COMMERCIAL FISH MEAL DRYER - RAO, D RAMANANDA; KAMASASTRI, P V (Fishery Technology, 2025)
The physical and chemical compositions of the raw materialsreceived and the composition and nutritive values of the finished productsin a commercial size fish meal plant employing the dry renderingprocess were studied and reported in this paper.